Metformin Combining PD-1 Inhibitor Enhanced Anti-Tumor Efficacy in STK11 Mutant Lung Cancer Through AXIN-1-Dependent Inhibition of STING Ubiquitination - Wang, Zhiguo; Lu, Conghua; Zhang, Kejun; Lin, Caiyu; Wu, Fang; Tang, Xiaolin; Wu, Di; Dou, Yuanyao; Han, Rui; Wang, Yubo; Hou, Chao; Ouyang, Qin; et al. (Frontiers in Molecular Biosciences, 2022)
Background: Non-small-cell lung cancer (NSCLC) with STK11 mutation showed primary resistance to immune checkpoint inhibitors (ICIs). The glucose-lowering drug metformin exerted anti-cancer effect and enhanced efficacy of chemotherapy in NSCLC with KRAS/STK11 co-mutation, yet it is unknown whether metformin may enhance ICI efficacy in STK11 mutant NSCLC. Methods: We studied the impact of metformin on ICI efficacy in STK11 mutant NSCLC in vitro and in vivo using colony formation assay, cell viability assay, Ki67 staining, ELISA, CRISPR/Cas9-mediated knockout, and animal experiments. Results: Through colony formation assay, Ki67 incorporation assay, and CCK-8 assay, we found that metformin significantly enhanced the killing of H460 cells and A549 cells by T cells. In NOD-SCID xenografts, metformin in combination with PD-1 inhibitor pembrolizumab effectively decreased tumor growth and increased infiltration of CD8+ T cells. Metformin enhanced stabilization of STING and activation of its downstream signaling pathway. siRNA-mediated knockdown of STING abolished the effect of metformin on T cell-mediated killing of tumor cells. Next, we found that CRISPR/Cas9-mediated knockout of the scaffold protein AXIN-1 abolished the effect of metformin on T cell-mediated killing and STING stabilization. Immunoprecipitation and confocal macroscopy revealed that metformin enhanced the interaction and colocalization between AXIN-1 and STING. Protein-protein interaction modeling indicated that AXIN-1 may directly bind to STING at its K150 site. Next, we found that metformin decreased K48-linked ubiquitination of STING and inhibited the interaction of E3-ligand RNF5 and STING. Moreover, in AXIN-1−/− H460 cells, metformin failed to alter the interaction of RNF5 and STING. Conclusion: Metformin combining PD-1 inhibitor enhanced anti-tumor efficacy in STK11 mutant lung cancer through inhibition of RNF5-mediated K48-linked ubiquitination of STING, which was dependent on AXIN-1.